2011
DOI: 10.1007/s11434-011-4527-7
|View full text |Cite
|
Sign up to set email alerts
|

Nano-sized graphitic carbon in authigenic tube pyrites from offshore southwest Taiwan, South China Sea, and its implication for tracing gas hydrate

Abstract: Gas hydrates are a significant energy resource and are usually detected by bottom simulating reflection and submarine geochemical anomalies. Authigenic minerals are related to gas hydrates, with carbonates, sulfates and sulfides being important tracing minerals. Authigenic tubular pyrites were collected from offshore southwest Taiwan in the South China Sea, and were investigated by scanning electron microscopy(SEM) and high-resolution transmission electron microscopy (HRTEM). Authigenic tubular pyrite was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In recent years, many gas hydrate cold seeps have been found in the northern South China Sea. Occurrences of gas hydrates by the observation of BSRs and cold seeps have also been reported in southwestern Taiwan [43][44][45]. Chen et al [46] reported for the first time the occurrence of carbonates originating from cold seeps in the South China Sea and showed that those carbonates probably formed at presently active gas seepage sites.…”
Section: Geological Settingmentioning
confidence: 91%
“…In recent years, many gas hydrate cold seeps have been found in the northern South China Sea. Occurrences of gas hydrates by the observation of BSRs and cold seeps have also been reported in southwestern Taiwan [43][44][45]. Chen et al [46] reported for the first time the occurrence of carbonates originating from cold seeps in the South China Sea and showed that those carbonates probably formed at presently active gas seepage sites.…”
Section: Geological Settingmentioning
confidence: 91%
“…Except for the individual crystal, pyrite microcrystals are mostly found assembled as framboids [37]. [38][39][40][41][42], octahedral form [8,38,[43][44][45], pyritohedral form [12,38,43,[45][46][47], and intermediate [13,33,44,48,49] [38][39][40][41][42], octahedral form [8,38,[43][44][45], pyritohedral form [12,38,43,[45][46][47], and intermediate [13,33,44,48,49] under different marine environments, among which (O6,C5,C6,I1,I5,P5,P6) are BSE images, (O1-O5, C1-C4,I2-I4,I6,P1-P4) are SE images.…”
Section: Shape Of Single Crystal Of Pyritementioning
confidence: 99%
“…Previous studies revealed a sequence of morphology evolution of pyrite crystals [7] and pyrite aggregates [8], the morphological characteristics and size distribution of pyrite in normal marine sediment [9][10][11] and in sulfate-methane transition zone (SMTZ) [12][13][14], the various growth conditions during pyrite formation [15]. The morphology of pyrite provides important scientific significance for studying marine sedimentary successions, tracking microbial activities, and diagenetic processes [9,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations